Predictors of mortality at 3 months in patients with skull base tumor resections in a low-income setting - Shiferaw, Mestet Yibeltal; Baleh, Abat Sahlu; Gizaw, Abel; Teklemariam, Tsegazeab Laeke; Aklilu, Abenezer Tirsit; Awedew, Atalel Fentahun; Anley, Denekew Tenaw; Mekuria, Bereket Hailu; Yesuf, Ermias Fikiru; Yigzaw, Mengistu Ayele; Molla, Henok Teshome; Awano, Mekides Muse; et al. (Frontiers in Surgery, 2024)
Objective: Globally, skull base tumors are among the most challenging tumors to treat and are known for their significant morbidity and mortality. Hence, this study aimed to identify associated factors that contribute to mortality of patients following surgical resection for a variety of skull base tumors at 3 3-month follow-up period. This in turn helps devise an evidence-based meticulous treatment strategy and baseline input for quality improvement work. Methodology: A retrospective cohort study of patients undergoing skull base tumor resection was conducted at two large-volume neurosurgery centers in Ethiopia. Categorical variables were expressed in frequencies and percentages. Normal distribution of continuous data was checked by histogram and Shapiro-Wilk test. Median with interquartile range (IQR) was calculated for skewed data while mean with standard deviation (SD) was used for normally distributed data. Odds ratio and adjusted odds ratio was used to express the result of univariate and multivariate binary logistic analysis respectively. A p-value <0.005 were considered statistically significant at 95% confidence interval. The study involved 266 patients. Of this, females accounted for 63.5 % of patients. The median age of patients was 37 (±IQR=17) years while the median size of the tumor in this study was 4.9 (± IQR 1.5). The mean duration of symptoms at time of presentation was 17.3 months (±SD = 11.1). Meningioma, pituitary adenoma, and craniopharyngioma contributed for 68.4%, 19.2% and 9% of the skull base tumors respectively. Mortality following skull base tumor resection was 21.1 %. On multivariable binary logistic regression analysis, intraoperative iatrogenic vascular insult (AOR=28.76, 95% CI: 6.12-135.08, p=0.000), intraventricular hemorrhage (IVH) (AOR=6.32, 95% CI: 1.19-33.63, p=0.031), hospital-associated infection (HAI) (AOR=6.96, 95% CI: 2.04-23.67, p=0.002), and extubation time exceeding 24 hours (AOR=12.89, 95% CI: 4.89-40.34, p=0.000) were statistically significant with 3-month mortality. Mortality from skull base tumor resection remains high in our setting. Holistic preoperative surgical planning, meticulous intraoperative execution of procedures, and postoperative dedicated follow-up of patients in a neurointensive care unit alongside quality improvement works on identified risks of mortality is strongly recommended to improve patients' outcomes. The urgent need for setup improvement and further training of neurosurgeons is also underscored.